2023
DOI: 10.3390/medicina59071234
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Look at Hashimoto’s Disease, Adrenal Incidentalomas, Obesity and Insulin Resistance—Could Endocrine Disruptors Be the Other Side of the Same Coin?

Abstract: Hashimoto’s disease (HD) is the most common cause of hypothyroidism in developed countries. The exact pathomechanism behind it has not been clearly established; however, an interplay of genetic susceptibility, environmental triggers (including diet) and epigenetic factors seems to be involved. Among the latter, increasingly more attention has been paid to some hormonally active substances, known as endocrine disruptors, which are commonly used worldwide. HD has become a condition widely reported in the media, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
0
0
Order By: Relevance
“…While genetic factors and lifestyle choices contribute to IR, emerging research suggests that EDCs may also play a role in its development. Numerous epidemiological studies have investigated the association between EDC exposure and IR [6][7][8]. The reviewed studies have identified several classes of EDCs that may contribute to this metabolic condition, including pesticides, polychlorinated biphenyls, bisphenol A (BPA), phthalates, polycyclic aromatic hydrocarbons (PAH), and dioxins.…”
Section: Review Ir and Endocrine Disruptionmentioning
confidence: 99%
“…While genetic factors and lifestyle choices contribute to IR, emerging research suggests that EDCs may also play a role in its development. Numerous epidemiological studies have investigated the association between EDC exposure and IR [6][7][8]. The reviewed studies have identified several classes of EDCs that may contribute to this metabolic condition, including pesticides, polychlorinated biphenyls, bisphenol A (BPA), phthalates, polycyclic aromatic hydrocarbons (PAH), and dioxins.…”
Section: Review Ir and Endocrine Disruptionmentioning
confidence: 99%